2013
DOI: 10.1080/00103624.2012.747610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seeding Date and Growing Season Conditions on Forage Yield and Quality of Four Annual Crops in Northeastern Saskatchewan

Abstract: Field experiments were conducted in 2002 and 2003 on a Black Chernozem (Udic Boroll) silty clay soil at Melfort, Saskatchewan, to determine the effects of seeding date on forage dry-matter yield (DMY) and quality [protein and acid detergent fiber (ADF) contents] of four annual crops [barley (Hordium vulgare L.), oat (Avena sativa L.), triticale (× Triticosecale Wittmack L.), and foxtail millet (Setaria italica L. Beauv; hereafter called Golden German millet)] with various maturities as well as different growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The low yield of the oil (12.5 %) compared to those recorded in previous studies; 21.6 % [9], 15.61% [14], 21.0 % [15] might be attributed to various factors such as the differences in the genetic make-up of the plants, maturity of the plant at time of collection and place of collection of the plant materials [16], and also mode of extraction employed in the different studies. Hence, there is need for optimization of extraction process prior to large scale seed valorization.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The low yield of the oil (12.5 %) compared to those recorded in previous studies; 21.6 % [9], 15.61% [14], 21.0 % [15] might be attributed to various factors such as the differences in the genetic make-up of the plants, maturity of the plant at time of collection and place of collection of the plant materials [16], and also mode of extraction employed in the different studies. Hence, there is need for optimization of extraction process prior to large scale seed valorization.…”
Section: Discussionmentioning
confidence: 46%
“…The lower the acid value of oil, the fewer free fatty acids it contains which makes it less exposed to rancidity [14,16]. Acid value could also be used to check the level of oxidative deterioration of oil by enzymatic or chemical oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Protein content in forage may likely to decrease as dry matter yield increased (Foster & Malhi, 2013), the protein content in forage tended to be superior for the cereals with the early planting date and lowest existences to harvest. Acid Detergent Fiber (ADF) content of forage retorted inversely to protein content of forage, but has a tendency to increase as dry matter yield increased with increased days to harvest (Foster & Malhi, 2013). Widdicombe and Thelen (2002) reported that crude protein contents of forage maize were negatively related with plant density.…”
Section: Forage Yield and Qualitymentioning
confidence: 99%
“…The NDF and ADF contents are important in rations formulation because they reflect the amount of forage that can be used up by animals (Lithourgidis et al, 2006). Protein content in forage may likely to decrease as dry matter yield increased (Foster & Malhi, 2013), the protein content in forage tended to be superior for the cereals with the early planting date and lowest existences to harvest. Acid Detergent Fiber (ADF) content of forage retorted inversely to protein content of forage, but has a tendency to increase as dry matter yield increased with increased days to harvest (Foster & Malhi, 2013).…”
Section: Forage Yield and Qualitymentioning
confidence: 99%
“…However the forage acid detergent fiber (ADF) content responded inversely to the protein content of forage ADF showed increased tendency as dry matter yield increased with prolonged harvest days (Foster and malhi, 2013). Dry matter yield and CP of forages were improved using legume intercropps in comparison with the corn sole crop.…”
Section: Introductionmentioning
confidence: 88%